Toxicokinetics and Bioaccumulation of Polycyclic Aromatic Compounds in Wood Frog Tadpoles (Lithobates sylvaticus) Exposed to Athabasca Oil Sands Sediment - Bilodeau, Julie (Université d'Ottawa / University of Ottawa, 2017)
Many polycyclic aromatic compounds (PACs) are toxic, carcinogenic, and mutagenic. As a result, their effects on aquatic biota and ecosystems are of great concern. Research on PACs in aquatic biota often overlooks the role of amphibians, alkylated PACs, and sediment as an uptake route. In order to study the accumulation and toxicokinetics of PACs following sediment and aqueous exposure, and to compare the bioaccumulation potentials of parent and alkyl PACs, two accumulation-elimination experiments using wood frog tadpoles (Lithobates sylvaticus) of Gosner stage 28-32 were conducted (one evaluating exposure to contaminated sediment and water, and the other to contaminated water alone). A complementary field study was then conducted near Fort McMurray, Alberta to assess PAC body burdens in field-collected amphibian larvae, and to determine whether PAC body burdens are related to exposure to sediment and/or water in the field. The results of our studies showed that PAC concentrations and uptake rates in wood frog tadpoles were highest when they were exposed to PAC-contaminated sediment. Consequently, we determined that the dominant route of exposure of wood frog tadpoles to PACs is sediment rather than water. This finding supports other studies that have shown dietary uptake to be an important route of PAC exposure in other aquatic organisms. In both the laboratory and field study, alkyl PAC concentrations exceeded those of parent PACs in wood frog tadpoles, which also demonstrated petrogenic PAC profiles. Interestingly, parent PACs seemed to have greater bioaccumulation potential than alkyl PACs in the laboratory-exposed wood frog tadpoles (in relation to sediment), possibly due to greater bioavailability or lower metabolism of parent PACs or alternatively, due to a saturation in uptake of alkyl PACs. Nevertheless, only a few compounds, including anthracene, fluoranthene, retene, and C1-benzofluoranthenes/benzopyrenes, were found to have higher bioaccumulation potentials. Lithobates sylvaticus tadpoles seemed to be efficient at eliminating and metabolizing both parent and alkyl PACs. However, the elimination of some compounds, such as C4-naphthalenes, was not as efficient. Furthermore, C3-fluorenes and C2-dibenzothiophenes were isolated as potential markers of amphibian larvae exposure to PAC-contaminated sediment due to their positive correlation with the wetland sediment concentrations. Additional field collections in the Athabasca oil sands are warranted to verify the utility of these markers in the natural environment. Evidently, this thesis highlights the importance of including sediment exposure and alkylated PACs in toxicological and field studies of benthic and epibenthic organisms. The results of this study are the largest, most comprehensive set of toxicokinetic and bioaccumulation information of PACs (52 analytes) in the amphibian larvae Lithobates sylvaticus obtained to date.